Does the IMF help or hurt?: the effect of IMF programs on the likelihood and outcome of currency crises - Dreher, Axel; Walter, Stefanie (World development, 2010)
We empirically analyze the effect of International Monetary Fund (IMF) involvement on the risk of entering a currency crisis and, respectively, the outcome of such a crisis. Specifically, we investigate whether countries with previous IMF intervention are more likely to experience currency crises. In a second step, we analyze the IMF’s impact on a country’s decision to adjust the exchange rate, once a crisis occurs. We find that IMF involvement reduces the probability of a crisis. Once in a crisis, IMF programs significantly increase the probability that the authorities devalue the exchange rate. The amount of loans and compliance with conditionality have no impact.
Available online 9 July 2009
Gesehen am 17.04.2023
Keywords: Internationaler Währungsfonds; 1975-2002; Erde